Developmentscenarios using decision support system for cost of post-harvest phase of coffee - Santos, Rafael Vargas; Vieira, Henrique Duarte; Flávio, Borém Meira (Coffee Science - ISSN 1984-3909, 2015)
The choice of method of processing coffee is decisive on the profitability of the coffee activity, and will depend on several factors. Thus, due to the existence of many variables is common producer ask about the viability of certain types of processing. Thus, the objective of this study was to detail the proposed processing alternative to two farms more profitable. Forty-six farms in the regions of the Cerrado, Matas de Minas and southern of Minas Gerais state answered a questionnaire in order to enable this analysis. By employing the decision support system for the calculation of the coffee postharvest cost , it was found that 21 farms with original dry processing gain between R 26.5780 and R 35.9039 per bag of coffee produced if they chose the alternative wet processing . As for the 25 farms with original wet processing lose from R 1.28291 and R 7.26029 per bag of coffee produced, if they chose the alternative splicing via dry.